Pengaruh Ketidakpuasan Konsumen dan Harga terhadap Perpindahan Merek dengan Brand Image sebagai Variabel Mediasi: Studi Kasus Perpindahan dari Grab ke Gojek - Ratu Afifa Safiera; Wenny Pebrianti; Erna Listiana (MES Bogor, 2026)
Competition in the Indonesian online transportation industry is dominated by two major brands, Grab and Gojek. The phenomenon of brands switching from Grab to Gojek demonstrates the importance of understanding the factors that influence consumer behavior in choosing a service. This study aims to develop a conceptual model that explains the influence of consumer dissatisfaction and price on brand switching decisions, with brand image as a mediating variable. The ,ethod used is a literature review with a descriptive analytical approach. The result of the study indicate that dissatisfaction and price perception have a significant impact on brand switching intentions. However, brand image can moderats this influence by shaping consumers’ perceptions of trust and tolerance for service imperfections. The proposed conceptual model can serve as a basis for further quantitative research, with a populations of online transportation users who have croo-platform experience. These findings provide strategic implication for digital brand managers in strengthening consumer loyalty amidst homogeneous service competition.